Fisioterapia respiratória associada à terapia com surfactante no tratamento da síndrome de aspiração de mecônio em modelo experimental - Stivanin, Jaqueline Basso (2015)
Objectives: To assess the effect of chest physiotherapy associated with bronchoalveolar lavage with surfactant on the arterial blood gases analysis and radiological findings in an experimental model of meconium aspiration syndrome. Methods: Twelve newborn piglets with experimentally induced meconium aspiration syndrome were randomized into two groups according to the treatment to be given: the control group (which underwent bronchoalveolar lavage with surfactant, associated with change of decubitus and additional dose of surfactant); and the physical therapy group (subjected to the same procedures and added chest physiotherapy with the bag squeezing technique). Measurements of the arterial partial pressure of oxygen, partial pressure of carbon dioxide, and pH were performed before treatment and at 90 minutes and 150 minutes after treatment in both groups. The radiological examination was done soon after the last measurement of gases, prior to euthanasia. The statistical analysis used the Student t test for independent samples, Kolmogorov-Smirnov, ANOVA and Kruskal-Wallis tests. Differences were considered significant at p <0.05. Results: A good response in blood gases analysis was seen in both groups after treatment, with no differences between the groups throughout the study. Radiological examination revealed hyperinflation in 46.7% of lung lobes in the group receiving physiotherapy and in no lobe in the control group (p<0.001). The other radiological findings did not differ between the two groups. Conclusions: Chest physiotherapy did not provide additional benefits, when associated with bronchoalveolar lavage with surfactant, change of decubitus and additional dose of surfactant, in the treatment of experimentally induced meconium aspiration syndrome in newborn piglets.